PENGARUH TINGKAT SUKU BUNGA, JUMLAH BAGI HASIL, DANLQ 45 TERHADAP SIMPANAN MUDHARABAH PADA BANKSYARIAH DI INDONESIA - Yustitia Agil Reswari; Ahim Abdurahim (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
This research has a purpose to know the influence of interest, profit sharing, and LQ 45 to funding in Indonesian Syariah Bank Period 2006-2008. All trials in this research use the help of SPSS program. The trial of quality of data use Classic Assumption Test, whereas for the trial of hypothesis use multiple linier regression test consists oft-statistic test, determination R2 test, and statistic F test.The result of multiple linear regression test, thatis t-statistic test indicate that interest (BIrate) variable doesn't have an effect to funding. Profit sharing variable has a positive significant effect to funding, so that with LQ 45 has a positive significant effect to funding. Statistic F test explain that all of independent variabel (interest, profit sharing, and LQ 45) has an effect to funding, while for the trial of quality of data, explained that all of classic assumption test can be fulfilled.